Sosialisasi Dalam Meningkatkan Partisipasi Masyarakat Terkait Pemilihan Umum Desa Dutohe Melalui Kegiatan MBKM Pemilu - Melo, Ramla Hartini; Merlin, Merlin; Pambudi, Moch. Rio; Tue, Febriyani (Damhil: Jurnal Pengabdian kepada Masyarakat, 2024)
In increasing public participation in elections, the low level of citizen participation in the previous election process was caused by a lack of understanding, such as: about the importance of the right to vote and election procedures, as well as the digital divide which made it difficult for people to access information related to elections. This research aims to examine how socialization activities initiated by MBKM can increase community awareness and understanding of the importance of elections and motivate them to actively participate in the democratic process at the village level, especially Dotuhe village. This study was conducted using qualitative research methodology with library study methods. research), which focuses on collecting and analyzing secondary data to produce accurate and relevant information. The results of the research show that socialization through MBKM Election activities is effective in increasing public participation in elections. This is proven by the increase in the number of voters in the presidential election in Dutohe village in 2024 compared to the previous year. Apart from that, MBKM Election activities also help increase public awareness about the importance of elections and raise their voices and their role in determining the country's leaders.